Assessment of nutritional status, abdominal obesity and level of physical activity among shift working female nurses in Hospital Universiti Sains Malaysia - Ming, Maria Wong Siaw (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Obesity is a global major health problem including Malaysia with the increasing of prevalence in abdominal obesity. The objective of this study was to assess nutritional status, abdominal obesity and level of physical activity among nurses working in Hospital Universiti Sains Malaysia (HUSM), Kelantan. This crosssectional study was conducted among 190 female nurses aged from 21 to 55 years old, who were systematically sampled from all wards by using the name list. Respondents were interviewed on sociodemographic characteristics, breakfast habit, sleep duration and night shift, dietary pattern and their level of physical activity. Weight, height, body mass index (BMI), waist-to-hip ratio and body fat percentage were measured, recorded and calculated. The mean BMI was 24.8 ± 5.1 and about half of the respondents (48.9%) were having normal body mass index (BMI), 43.3% were overweight and obese and 7.9% were underweight. Out of respondents, 78.0% had normal waist circumference whereas 62.6% had normal waist-to-hip ratio. In term of body fat, 48.9% had normal body fat percentage while 45.8% had high body fat percentage. All sociodemographic variables did not show any association with abdominal obesity except age (p=0.001). Further analaysis of simple linear regression showed, age, salary per month and number of children did have linear relationship and were predictors for abdominal obesity. Findings showed risk of abdominal obesity tend to increase with age among adult female nurses. Duration of sleep, night shift frequency, breakfast habit and physical activity level also did not show any significant association or linear relationship with abdominal obesity. In term of dietary pattern, sugar and white rice consumption was top two highest food items daily and 74.2% were breakfast skipper, but no association with abdominal obesity was found. In conclusion, larger sample size in different hospital setting with more homogenous sample in term of age should be considered in future study to identify the factors that are associated with the abdominal obesity.